Analyzing pre-symptomatic tissue to gain insights into the molecular and mechanistic origins of late-onset degenerative trinucleotide repeat disease. Issue 12 (28th May 2020) - Chu, Yongjun; Hu, Jiaxin; Liang, Hanquan; Kanchwala, Mohammed; Xing, Chao; Beebe, Walter; Bowman, C Bradley; Gong, Xin; Corey, David R; Mootha, V Vinod
Abstract: How genetic defects trigger the molecular changes that cause late-onset disease is important for understanding disease progression and therapeutic development. Fuchs' endothelial corneal dystrophy (FECD) is an RNA-mediated disease caused by a trinucleotide CTG expansion in an intron within the TCF4 gene. The mutant intronic CUG RNA is present at one–two copies per cell, posing a challenge to understand how a rare RNA can cause disease. Late-onset FECD is a uniquely advantageous model for studying how RNA triggers disease because: (i) Affected tissue is routinely removed during surgery; (ii) The expanded CTG mutation is one of the most prevalent disease-causing mutations, making it possible to obtain pre-symptomatic tissue from eye bank donors to probe how gene expression changes precede disease; and (iii) The affected tissue is a homogeneous single cell monolayer, facilitating accurate transcriptome analysis. Here, we use RNA sequencing (RNAseq) to compare tissue from individuals who are pre-symptomatic (Pre_S) to tissue from patients with late stage FECD (FECD_REP). The abundance of mutant repeat intronic RNA in Pre_S and FECD_REP tissue is elevated due to increased half-life in a corneal cells. In Pre_S tissue, changes in splicing and extracellular matrix gene expression foreshadow the changes observed in advanced disease and predict the activation of the fibrosis pathway and immune system seen in late-stage patients. The absolute magnitude of splicing changes is similar in pre-symptomatic and late stage tissue. Our data identify gene candidates for early drivers of disease and biomarkers that may represent diagnostic and therapeutic targets for FECD. We conclude that changes in alternative splicing and gene expression are observable decades prior to the diagnosis of late-onset trinucleotide repeat disease.